Securing your Ubuntu server. (O'Reilly Media, Inc., 2018)
What is this video course about, and why is it important? Since its inception, the Linux operating system has enjoyed tremendous popularity and an ever increasing installed base. One of the reasons for its success is because, out of the box, most Linux servers offer a fairly stable and secure environment. Ubuntu, which was released in 2004, has demonstrated itself to be among one of the more secure of the Linux distributions, owing to its built-in enterprise-grade security structure. But today, attackers are becoming ever more sophisticated in their attempts to penetrate your digital assets and steal valuable data, so it's always a good idea to take whatever steps you can to further secure that data residing on your Ubuntu servers. In this video course, host and prolific technology writer Jack Wallen introduces you to some of the basic and necessary steps for hardening an Ubuntu server. You'll see how to set up secure shared memory, use and enforce strong passwords, enable automatic security updates, configure two-factor authentication, and encrypt directories by using ecryptfs. You'll also learn why you should adopt the philosophy of installing only what you need on your Ubuntu server, limiting the applications and daemons running in the background and thus reducing your attack surface. If you're an entry- to intermediate-level system administrator or engineer, by following the steps explained in this tutorial, you can make your Ubuntu server considerably more secure. What you'll learn--and how you can apply it How to enable secure shared memory to prevent an attack against a running service on your Ubuntu Server Enable SSH login for specific users to prevent unauthorized access via secure shell Add a security login banner to serve as a warning to unwanted users Use and enforce strong passwords to prevent users from making use of weak passwords How to encrypt directories with ecryptfs to aid in the protection of your data How to enable automatic security updates, to keep you from missing crucial patches How to install only what you want, so there aren't extraneous daemons and applications running in the background that can be exploited How to enable two-factor authentication for your Ubuntu server to prevent unwanted users from logging in This video course is for you because... You're a security engineer or a system administrator who needs to roll out an Ubuntu-based server and want to make it as secure as possible You're debating whether a Linux server is the right fit for you and your company and want to learn if there are steps you can take to better secure it You're a new administrator or security professional (or a student) and you want to see how easy it is to manage the security of an Ubuntu server Prerequisites: You should have a basic understanding of Linux and general security principles You should know how to use the command line You should have access to a user with root privileges Materials or downloads needed in advance: Learning Path: Networking for Sysadmins Learning Path: Kali Linux.